2017
DOI: 10.1038/s41598-017-06581-6
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory anabolic signaling in the sarcopenia of experimental chronic arthritis

Abstract: Inflammatory activity in rheumatoid arthritis may alter the regulation of muscle mass leading to a secondary sarcopenia, commonly termed rheumatoid cachexia (RC). We characterized alterations to muscle structure and various pro-inflammatory, catabolic and regenerative markers in an animal model of RC. Antigen induced arthritis (AiA) was performed in 20 male adult rabbits. AiA animals exhibited significantly less weight gain, a markedly elevated serum C-reactive protein (CRP), lighter muscles with shorter cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 66 publications
3
31
0
Order By: Relevance
“…Our previous research demonstrated that these animals present up to a 30% decrease in myofiber diameter after 45 days of disease induction . In addition, a recently published study with autoimmune monoarthritis by AIA has shown several molecular analyses for muscle wasting observed in rabbits, including increased GA atrogin‐1 and MURF‐1 expression . The present study confirms that animals had muscle loss even if they did not lose weight.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our previous research demonstrated that these animals present up to a 30% decrease in myofiber diameter after 45 days of disease induction . In addition, a recently published study with autoimmune monoarthritis by AIA has shown several molecular analyses for muscle wasting observed in rabbits, including increased GA atrogin‐1 and MURF‐1 expression . The present study confirms that animals had muscle loss even if they did not lose weight.…”
Section: Discussionsupporting
confidence: 85%
“…22 In addition, a recently published study with autoimmune monoarthritis by AIA has shown several molecular analyses for muscle wasting observed in rabbits, including increased GA atrogin-1 and MURF-1 expression. 40 The present study confirms that animals had muscle loss even if they did not lose weight. It was observed by the less weigh in tibialis anterior and gastrocnemius muscles in the CIA group (decrease of 25 and 24%, respectively).…”
Section: Figuresupporting
confidence: 86%
See 1 more Smart Citation
“…Aging is associated with a chronic state of systemic low‐grade inflammation, characterized by increased plasma levels of pro‐inflammatory mediators like TNF‐α and IL‐6, which are able to stimulate proteolysis mainly via UPR, as previously described for cancer cachexia . However, the role of UPR in sarcopenia is still contentious . Some studies have described an up‐regulation of components of the UPR in sarcopenia while other have shown a down‐regulation or no differences …”
Section: Sarcopeniamentioning
confidence: 97%
“…Sarcopenia is classified by its etiology into primary or secondary sarcopenia. Primary sarcopenia is a phenomenon of age‐related loss of muscle mass and function, affecting up to 30% of older adults [4]. Secondary sarcopenia is the reduced muscle mass and strength that accompanies an underlying disease.…”
Section: Introductionmentioning
confidence: 99%